Se A = 2x + 4y + 5, B = 2x + 2y - 3 e C = +4x – y + 4, então A – B + C é igual a:,
Soluções para a tarefa
Respondido por
35
Resposta:
A - B + C = 4x + y + 12
Explicação passo-a-passo:
A = 2x + 4y + 5
B = 2x + 2y - 3
C = +4x – y + 4
A – B + C =
( 2x + 4y + 5) - (2x + 2y - 3) + (+4x – y + 4) =
2x + 4y + 5 - 2x - 2y + 3 + 4x – y + 4 =
4x + y + 12
Respondido por
7
Resposta:
+4x +y +12
Explicação passo-a-passo:
Perguntas interessantes
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Contabilidade,
10 meses atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás
Física,
1 ano atrás